Computational Drug Repurposing Approach to Identify Novel Inhibitors of ILK Protein for Treatment of Esophageal Squamous Cell Carcinoma. (29th December 2022) - Liu, Juan; Ma, Xiaoli; Cao, Leiyu; Wei, Yu; Gao, Yan; Qu, Chengcheng; Maimaitiming, Nuersimanguli; Zhang, Li
Abstract : Purpose . Esophageal squamous cell cancer (ESCC) is a deadly malignant tumor characterized by an overall 5-year survival rate below 20%, with China accounting for approximately 50% of all cases worldwide. Our previous studies have demonstrated that high integrin-linked kinase (ILK) expression plays a key role in development and progression of ESCC both in vitro and in vivo . Here, we employed the drug repurposing approach to identify a novel FDA-approved anticancer inhibitor against ILK-induced tumorigenesis and progression. Methods . We screened the ZINC15 database and predicted the molecular docking ability among FDA-approved and publicly available drugs to ILK and then performed computational docking and visual inspection analyses of the top 10 ranked drugs. Two computer-based virtual screened drugs were evaluated in vitro for their ability to directly bind purified ILK by surface plasmon resonance. Cytotoxicity of the two candidate drugs was validated in vitro using CCK-8 and LDH assays. Results . We initially selected the top 10 compounds, based on their minimum binding energy to the ILK crystal, after molecular docking and subjected them to further screening. Taking the binding energy of −10 kcal/mol as the threshold, we selected two drugs, namely, nilotinib and teniposide, for the wet-lab experiment. Surface plasmon resonance (SPR) revealed that nilotinib and teniposide had equilibrium dissociation constant (KD) values of 6.410 E − 6 and 1.793 E − 6, respectively, which were lower than 2.643 E − 6 observed in ILK-IN-3 used as the positive control. The IC50 values for nilotinib and teniposide in ESCC cell lines were 40 μ M and 200–400 nM, respectively. Results of the CCK-8 assay demonstrated that both nilotinib and teniposide significantly inhibited proliferation of cells (P < 0.01 ). LDH results revealed that both drugs significantly suppressed the rate of cell death (P < 0.01 ). Conclusion . The drug repositioning procedure can effectively identify new therapeutic tools for ESCC. Our findings suggest that nilotinib and teniposide are efficacious inhibitors of ILK and thus have potential to target ILK-mediated signaling pathways for management of ESCC.